Coronavirus disease (COVID-19). A bibliometric analysis [Nuevo coronavirus (COVID-19). Un análisis bibliométrico] - O´Brien, Nicolás (2020)
ABSTRACT Objective: The new coronavirus pandemic (COVID-19) has spread to 180 countries, causing more than half a million confirmed cases and more than 40 thousand deaths. The main objective of this study was to analyze the world scientific production related to COVID-19. Material and Method: A literature search was performed using the Scopus database. A total of 547 published documents were identified, analyzing characteristics such as: type of publication, collaboration index, most productive countries, scientific journals, the institutions that are publishing the most on the subject and indicators of citations and impact. Results: China was ranked first with 213 published documents (20.9%). Regarding the journals with the higher number of published documents, these were The Lancet, British Medical Journal and the Journal of Medical Virology. Likewise, Wuhan University was identified as the institution presenting the highest leadership regarding the number of publications. The total number of citations for all the publications was of 1.685. The h-index of the retrieved articles was of 42, and four articles were found with more than 100 quotations. Conclusions: This study offers a first approach to the global efforts aimed to this new area of research, which in only three months has substantially increased, and is expected to remain being prolific.